A hedonic value-based consumercontinuance intention modeltoward location-based advertising (REGE Revista de Gestão, 2024)
Purpose–Hedonic value is commonly conceded as a determinant of behavioral intentions toward location-based advertising (LBA). However, the careful consideration of a mechanism behind hedonic motivation and its subsequent impact on continuance intention is inadequate. This study explores the formation of hedonic value and its motivation for prolonged usage toward LBA.Design/methodology/approach–A sample of 486 mobile users was recruited to evaluate the research model using structural equation modeling (SEM).Findings–Results reveal that perceived utility and promotional offers are the strongest indicators of hedonic value. Moreover, social support and contextual convenience play an essential role in heightening hedonic value. Furthermore, the research lenses attempt to clarify the direct, indirect influences of hedonic value, irritation and perceived credibility on continuance intention.Practical implications–The findings offer practitioners an understanding of how to improve hedonic value and continuance intention and develop effective LBA strategies in emerging markets.Originality/value–This study narrows the gap of current literature by formulating a hedonic value-based continuance intention model based on uses and gratifications theory (UGT). Additionally, this work illuminates the insights into hedonic value toward LBA by identifying its motivations, including perceived utility, promotional offers, social support, and contextual convenience.